Pengaruh Etika Auditor, Pengalaman, Due Professional Care, dan Perilaku Disfungsional terhadap Kualitas Audit (Studi Empiris pada Auditor KAP di Jawa Tengah dan DIY) - Restuwati, Martin, Drs. Suyatmin Waskito Adi, M.Si (2015)
The purpose of this study is to analyze and to provide empirical evidene about the effect of ethics of auditors, experience, due pofessional care, and dysfunctional behavior on quality of audit. The population in this research are auditors who work in the public accountant office in Jawa Tengah and DIY. The sampling method used is purposive sampling. The research data was obtained from questionnaires. The data analysis method used is multiple linear regression analysis, where ethics of auditors, experience, due pofessional care, and dysfunctional behavior as independent variable while quality of audit as dependent variable. The results of this study indicate that the ethics of auditors, experience, due pofessional care, and dysfunctional behavior have significant effect on audit of quality. This research also proves that ethics of auditors and due professional care partially influence on audit of quality, when experience and dysfunctional behavior partially not affect on audit of quality.